Analysis Multilevel: Application of Health Belief Model on Tertiary Prevention Behavior in Kaur District, Bengkulu Province, Indonesia - Betriza; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2025)
Background: Uncontrolled hypertension can cause complications, so efforts to prevent and control hypertension can be carried out by applying the Health Belief Model health promotion theory. This study aimed to determine the influence of the Health Belief Model construct on tertiary prevention behavior in hypertensive patients. Subjects and Method: This was a cross-sectional study conducted in 16 health centers in Kaur district, Bengkulu, from November to December 2023. A total of 208 hypertension patients were selected by simple random sampling. The dependent variable is tertiary prevention behavior. Independent variables are a number of constructs in the Health Belief Model theory including perceived susceptibility, stimulus to act, and self-efficacy. Data collection was carried out using questionnaires and data were analyzed using a multilevel double linear regression analysis model. Results: There was a positive association between perception of vulnerability (b= 0.11; CI 95%= 0.01 to 0.22; p= 0.065), signal to act (b= 0.20; CI 95%= 0.03 to 0.38; p= 0.022), self-efficacy (b= 0.16; CI 95%= -0.01 to 0.32; p= 0.059) on hypertension tertiary prevention behavior. Public health center have less contextual influence on tertiary prevention behavior in hypertensive patients (ICC= 6.68%). Conclusion: Perception of vulnerability, cues to act, and self-efficacy are predictors of hypertension tertiary prevention behaviors.